Beginning mobile application development in the cloud - Rodger, Richard (Wrox programmer to programmer, 2011)
Learn how to build apps for mobile devices on Cloud platforms The marketplace for apps is ever expanding, increasing the potential to make money. With this guide, you'll learn how to build cross-platform applications for mobile devices that are supported by the power of Cloud-based services such as Amazon Web Services. An introduction to Cloud-based applications explains how to use HTML5 to create cross-platform mobile apps and then use Cloud services to enhance those apps. You'll learn how to build your first app with HTML5 and set it up in the Cloud, while also discovering how to use jQuery to your advantage. * Highlights the skills and knowledge you need to create successful apps for mobile devices with HTML5 * Takes you through the steps for building web applications for the iPhone and Android * Details how to enhance your app through faster launching, touch vs. click, storage capabilities, and a cache * Looks at how best to use JSON, FourSquare, jQuery, AJAX, and more * Shares tips for creating hybrid apps that run natively If you're interested in having your application be one of the 200, 000+ apps featured in the iPhone store or the 50, 000+ in the Android store, then you need this book.